95% PREVALENCE OF ABNORMALITY ON HIP MRI IN ELITE ACADEMY LEVEL RUGBY UNION; A CLINICAL AND IMAGING STUDY OF HIP DISORDERS. Issue 4 (1st February 2017) - Farrell, Gareth; Wilson, F; Denvir, K; O'Connell, B; Irwin, E; Gissane, C; McGrath, F
Abstract : Background: Hip disorders are common in field based athletes. To date there have been no studies profiling hips in elite level rugby. Objective: Identify the prevalence of hip disorders (clinical and imaging) in elite academy rugby union players comparing to active controls. Design: Cross-sectional, case-control study. Setting: Professional Rugby Union Club. Patients (or Participants): 20 male professional Rugby Academy players and 20 age, activity and gender matched controls. Exclusion criteria were previous hip surgery, or hip, groin, or lumbar pathology within the previous six months. Interventions (or Assessment of Risk Factors): Participants were assessed on a single day using a HAGOS questionnaire, clinical tests (FABER and Thomas Test) and range of motion of the hip. The rugby playing cohort underwent dedicated non-arthrographic 3T MRI of the hip in three plains. Images were blind reviewed by two experienced musculoskeletal radiologists. Controls were clinically tested only. Main Outcome Measurements: Prevalence of hip Symptoms (HAGOS), clinical tests and range of motion of the hip and prevalence of abnormality on MRI. Results: The rugby cohort had significantly reduced hip rotation range, extension and FABER scores compared to the controls. Symptoms were reported by 65% of rugby players versus 15% in controls. There was a 95% prevalence of abnormality on MRI, 80% labral pathology, 60% CAM deformity and 25% had chondral wear. Conclusions: There was a high prevalence of hip abnormality (95%) on MRI in rugby players (80% labral pathology, 60% CAM defect). The percentage reporting symptoms was lower at 65% although this was significantly higher than (non-rugby) matched controls at 15%. Rugby players demonstrated significantly reduced range of movement of the hip compared to controls. Further prospective research is required.